Metformin Combining PD-1 Inhibitor Enhanced Anti-Tumor Efficacy in STK11 Mutant Lung Cancer Through AXIN-1-Dependent Inhibition of STING Ubiquitination - Wang, Zhiguo; Lu, Conghua; Zhang, Kejun; Lin, Caiyu; Wu, Fang; Tang, Xiaolin; Wu, Di; Dou, Yuanyao; Han, Rui; Wang, Yubo; Hou, Chao; Ouyang, Qin; et al. (Frontiers in Molecular Biosciences, 2022)
Background: Non-small-cell lung cancer (NSCLC) with STK11 mutation showed primary resistance to immune checkpoint inhibitors (ICIs). STK11 mutation leads to increased sensitivity of cancer cells to metformin, yet it is unknown whether metformin may enhance ICIs efficacy in STK11 mutant NSCLC. Methods: We studied the impact of metformin on ICI efficacy in STK11 mutant NSCLC in vitro and in vivo using colony formation assay, cell viability assay, Ki67 staining, ELISA, CRISPR-Cas9-mediated knockout, and animal experiments. Results: Through colony formation assay, Ki67 incorporation assay, and CCK-8 assay, we found that metformin significantly enhanced the killing of H460 cells and A549 cells by T cells. In NOD-SCID xenografts, metformin in combination with PD-1 inhibitor pembrolizumab effectively decreased tumor growth and increased infiltration of CD8+ T cells. Metformin enhanced stabilization of STING and activation of its downstream signaling pathway. siRNA-mediated knockdown of STING abolished the effect of metformin on T cell-mediated killing of tumor cells. Next, we found that CRISPR/Cas9-mediated knockout of the scaffold protein AXIN-1 abolished the effect of metformin on T cell-mediated killing and STING stabilization. Immunoprecipitation and confocal macroscopy revealed that metformin enhanced the interaction and colocalization between AXIN-1 and STING. Protein-protein interaction modeling indicated that AXIN-1 may directly bind to STING at its K150 site. Next, we found that metformin decreased K48-linked ubiquitination of STING and inhibited the interaction of E3-ligand RNF5 and STING. Moreover, in AXIN-1-/- H460 cells, metformin failed to alter the interaction of RNF5 and STING. Conclusion: Metformin combining PD-1 inhibitor enhanced anti-tumor efficacy in STK11 mutant lung cancer through inhibition of RNF5-mediated K48-linked ubiquitination of STING, which was dependent on AXIN-1.